Dietary patterns: What's in a name? - Boushey, Carol; Abed, B.; Corpuz, G.; Spoden, M. (2017)
The focus for quantifying dietary exposures hasmoved from single nutrients or foods to dietary patterns. These more comprehensive characterizations of the diet account for the synergistic effects of nutrients and allow for better translation to dietary recommendations for the broad public. Dietary patterns narrow down large amounts of nutrition information and usually apply amoniker, such as "Western diet" or "healthy diet." This leads to the question, what is in those names? Because of a missing standardized naming system for food patterns, not only individuals but also professionals have different definitions of single dietary patterns leading to confusion and ensuing erroneous assumptions. This article demonstrates the shortcomings regarding nomenclature with reference to 10 examples of the Western diet.